Analisis Kebutuhan Pengembangan E-Modul Flipbook Berbasis Deep Learning Pada Materi Sistem Peredaran Darah Kelas VIII Smp - Siregar, Ade Siti Khairunnisa; Hidayati, Nurkhairo (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to analyze the need for developing a deep learning–based flipbook e-module on the circulatory system material for Grade VIII junior high school students. The research employed a quantitative descriptive approach conducted at SMP Negeri 1 Siak Hulu, involving one science teacher and 30 students of class VIII-B as research subjects. Data were collected through teacher interviews and student questionnaires. The results indicate that the need for instructional media falls into the “needed” category (70%), material suitability (73%), student engagement and interest (73.3%), and media effectiveness (68.2%). The results of the teacher interviews support all findings obtained from the student questionnaires. Therefore, the development of a deep learning–based flipbook e-module is highly necessary to support more effective and meaningful biology learning.